Condrogênese de células tronco mesenquimais derivadas de Rattus Norvegicus utilizando matriz orgãnica tridimensional à base de quitosana - Natalia Martins Breyner (2006)
Cartilage is known to be an avascular tissue and this characteristic taken together with others provides the tissue a very limited regeneration capacity. Consequently, a small damage to the tissue results in progressive damages or degenerative processes like osteoarthrite. Tissue engineering techniques has been applied not only in the treatment of cartilage damage but also in other medical fields such as orthopedic and odontology. In the present work, it was demonstrated that the 3D (tridimesional) chitosan scaffold was efficient in the adhesion and differentiation process of the MSCs (Mesenchymal Stem Cells) after the addition of a chondrogenic medium containing TGF- and dexamethasone. The cultured MSCs in the 3D chitosan scaffold were more viable during the first nine weeks of culture, demonstrating a reduction in the production of Alkaline Phosphastase, which indicates phenotipic changes of the cells. Confirming these results, the collagen production of the MSCs cultured in this kind of scaffold increased together as the culture period indicating the beginning of a differentiation. However, when gelatin is added to the scaffold constitution, the results were not satisfactory. Ahead of the excellent results using a matrix made of chitosan in the promotion of MSCs differentiation. It becomes clear that this 3D organic structure is one of the best candidates for biomaterial implants colonized by stem cells in the tissue recovering in regenerative medicine.